Makna Tari Alang Suntiang Pangulu Dalam Upacara Batagak Pangulu Di Nagari Padang Laweh Kecamatan Sungai Pua Kabupaten Agam - Riri Fadri Azhari; Afifah Asriati (FBS Universitas Negeri Padang, 2020)
This study aims to describe the meaning of Alang Suntiang Pangulu dance in Padang Laweh village, Sungai Pua district, Agam regency. This is a qualitative research with a descriptive analysis method. The object of this research was Alang Suntiang Pangulu dance in Padang Laweh village, Sungai Pua district, Agam regency. The main instrument used was the researcher itself and was assisted by tools such as stationery and cameras to collect data in the field. The data were collected through literature study, observation, interview, and documentation. The data analysis was conducted by reducing the data, describing the data, and making conclusion.The results show that Alang Suntiang Pangulu dance describes lessons about things a Pangulu (a leader) uses to maintain his crown or honor. These are found in Alang Suntiang Pangulu dance which gives textual meanings elaborated through motion, floor patterns, music, dancers, make-up, performance, and venues.